Surprising performance of alginate beads for the release of low-molecular-weight drugs - Elnashar, Magdy; Yassin, M.; El-Fetouh Abdel Moneim, A.; Bary, E. (John Wiley and Sons Inc, 2010)
The model of low-molecular-weight drugs has been encapsulated within alginate beads hardened with calcium chloride. The drug's release kinetic using 3% (w/v) alginate has shown a surprising behavior after 2 h, where the release kinetic was shifted from Fickian to case II transport mechanism contradicting other authors like Akihiko et al. (J Control Release 1999, 58, 21). To support this finding, we studied the swelling of dried gel beads of 2 and 3% (w/v) alginate, which showed a sudden decrease in the swelling of 3% (w/v) alginate after 2 h due to a partial bursting of the beads. This sudden bursting was clearly observed using the optical microscope to emphasize the new findings. Calcium alginate beads revealed pH sensitivity, where 2% (w/v) alginate beads showed a maximum swelling of 5000% in alkaline medium at pH 7.4, compared with a negligible swelling percent of 60% in acidic medium (pH 1.2). Accordingly, it could be a good candidate for targeting smart and low-molecular-weight drugs to the intestine. © 2010 Wiley Periodicals, Inc.